Educational Opportunities for Students with Disabilities: The Experience of a University Student in Brunei - Faridah Serajul Haq (UiTM Publisher, 2007)
In Brunei, increased numbers of children with disabilities have been given educational opportunities in appropriate programs in schools. Students with disabilities have also succeeded in qualifying for higher studies on completing secondary education. However, there is a need for local university and colleges to cater to the specific needs of students with disabilities. This paper describes the experiences of a student with visual disabilities in Universiti Brunei Darussalam. The student emphasised his use of compensatory learning strategies, the accommodation available on campus, peer relationships and self-advocacy to communicate his needs. The support given to the student facilitated his academic success. The student is fully aware of his capabilities and his positive self-esteem has helped to overcome various setbacks. It is hoped that the information provided in this article will foster improvement in providing facilities for students with disabilities to learn in comfort and for the future enrollment of more students with special needs.